2016
DOI: 10.12788/jcso.0247
|View full text |Cite
|
Sign up to set email alerts
|

Reaching high-risk underserved individuals for cancer genetic counseling by video-teleconferencing

Abstract: Background Breast and colorectal cancers are common cancers for which genetic risk assessment and counseling are available. However, these services are often limited to metropolitan areas and are not readily accessible to underserved populations. Moreover, ethnic and racial disparities present additional obstacles to identifying and screening high-risk individuals and have a bearing on treatment outcomes. Objective To provide cancer genetic risk assessment and counseling through telemedicine to the remote, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…When examining the literature specific to genetics consultation via live videoconferencing, the term “telegenetics,” is most often used, but the terms “virtual health” (Weissman, Zellmer, Gill, & Wham, 2018), “televideo” (Voils et al, ), and web‐based/video (National Society of Genetic Counselors, ) were also noted. Collectively, these studies have demonstrated improved access to care in underserved areas with high levels of patient satisfaction and outcomes similar to in‐person consultations across many patient populations and medical indications (Abrams & Geier, ; Bradbury et al, ; Buchanan et al, ; Coelho, Arnold, Nayler, Tischkowitz, & MacKay, ; D'Agincourt‐Canning et al, ; Fournier, Bazzell, & Dains, ; Gattas, MacMillan, Meinecke, Loane, & Wootton, ; Gray et al, ; Hardy & Grinzaid, ; Hawkins, Creighton, Ho, McManus, & Hayden, ; Hilgart et al, ; Hopper, Buckman, & Edwards, ; Kubendran, Sivamurthy, & Schaefer, ; Lea et al, ; Mette et al, ; Otten, Birnie, Lucassen, Ranchor, & van Langen, ; Schwartz et al, ; Solomons, Lamb, Lucas, McDonald, & Miesfeldt, ; Stalker et al, ; Sutphen et al, ; Weissman et al, ; Wenger et al, ; Zilliacus et al, ; Zilliacus, Meiser, Lobb, Kirk, et al, ). Some studies have shown reductions in cost and time per patient for the clinic and/or the patient (Buchanan et al, ; D'Agincourt‐Canning et al, ; Otten, Birnie, Ranchor, & van Langen, ; Schwartz et al, ; Weissman et al, ), shorter wait times (Cohen et al, ; Kubendran et al, ; Stalker et al, ; Weissman et al, ), and a larger geographic reach (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining the literature specific to genetics consultation via live videoconferencing, the term “telegenetics,” is most often used, but the terms “virtual health” (Weissman, Zellmer, Gill, & Wham, 2018), “televideo” (Voils et al, ), and web‐based/video (National Society of Genetic Counselors, ) were also noted. Collectively, these studies have demonstrated improved access to care in underserved areas with high levels of patient satisfaction and outcomes similar to in‐person consultations across many patient populations and medical indications (Abrams & Geier, ; Bradbury et al, ; Buchanan et al, ; Coelho, Arnold, Nayler, Tischkowitz, & MacKay, ; D'Agincourt‐Canning et al, ; Fournier, Bazzell, & Dains, ; Gattas, MacMillan, Meinecke, Loane, & Wootton, ; Gray et al, ; Hardy & Grinzaid, ; Hawkins, Creighton, Ho, McManus, & Hayden, ; Hilgart et al, ; Hopper, Buckman, & Edwards, ; Kubendran, Sivamurthy, & Schaefer, ; Lea et al, ; Mette et al, ; Otten, Birnie, Lucassen, Ranchor, & van Langen, ; Schwartz et al, ; Solomons, Lamb, Lucas, McDonald, & Miesfeldt, ; Stalker et al, ; Sutphen et al, ; Weissman et al, ; Wenger et al, ; Zilliacus et al, ; Zilliacus, Meiser, Lobb, Kirk, et al, ). Some studies have shown reductions in cost and time per patient for the clinic and/or the patient (Buchanan et al, ; D'Agincourt‐Canning et al, ; Otten, Birnie, Ranchor, & van Langen, ; Schwartz et al, ; Weissman et al, ), shorter wait times (Cohen et al, ; Kubendran et al, ; Stalker et al, ; Weissman et al, ), and a larger geographic reach (Cohen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…access, genetic counseling, genetic services, rural, service delivery, telegenetics, telehealth, telemedicine, telephone counseling, underserved Fournier, Bazzell, & Dains, 2018;Gattas, MacMillan, Meinecke, Loane, & Wootton, 2001;Gray et al, 2000;Hardy & Grinzaid, 2017;Hawkins, Creighton, Ho, McManus, & Hayden, 2013;Hilgart et al, 2012;Hopper, Buckman, & Edwards, 2011;Kubendran, Sivamurthy, & Schaefer, 2017;Lea et al, 2005;Mette et al, 2016;Otten, Birnie, Lucassen, Ranchor, & van Langen, 2016;Schwartz et al, 2014;Solomons, Lamb, Lucas, McDonald, & Miesfeldt, 2018;Stalker et al, 2006;Sutphen et al, 2010;Weissman et al, 2018;Wenger et al, 2014;Zilliacus et al, 2011;Zilliacus, Meiser, Lobb, Kirk, et al, 2010). Some studies have shown reductions in cost and time per patient for the clinic and/or the patient (Buchanan et al, 2015;D'Agincourt-Canning et al, 2008;Otten, Birnie, Ranchor, & van Langen, 2016;Schwartz et al, 2014;Weissman et al, 2018), shorter wait times (Cohen et al, 2013;Kubendran et al, 2017;Stalker et al, 2006;Weissman et al, 2018), and a larger geographic reach (Cohen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 119 survey respondents, 16% were found to have a pathogenic mutation and 10% were found to have a variant of uncertain significance (VUS). 6 However, this study did not delineate if there was a difference in the uptake of genetic testing between the patients seen for in-person genetic counselling versus those seen for telegenetic counselling. Bradbury et al (2016) evaluated patients who were offered telegenetic counselling for hereditary cancer at two remote sites.…”
Section: Introductionmentioning
confidence: 87%
“…1 Studies have shown that when telegenetic counselling services are compared to inperson genetic counselling, outcomes are similar in terms of patient satisfaction, anxiety, cancer worry, and knowledge. [2][3][4][5][6][7][8][9] Cancer centres that do not currently employ a genetic counsellor are encountering an increasing need to provide genetic counselling services at their centres, due to requirements for accreditation and from insurance companies. The Commission on Cancer and the National Accreditation Program for Breast Centres both require access to cancer risk assessment and testing when indicated for program accreditation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation